Synthesis of Platinum(II) Complexes with Some 1-Methylnitropyrazoles and In Vitro Research on Their Cytotoxic Activity - Henryk Mastalarz; Agnieszka Mastalarz; Joanna Wietrzyk; Magdalena Milczarek; Andrzej Kochel; Andrzej Regiec (MDPI AG, 2020)
A series of eight novel platinum(II) complexes were synthesized by the reaction of the appropriate 1-methylnitropyrazole derivatives with K2PtCl4 and characterized by elemental analysis, ESI MS spectrometry, 1H NMR, 195Pt NMR, IR and far IR spectroscopy. Thermal isomerization of cis-dichloridobis(1-methyl-4-nitropyrazole)platinum(II) 1 to trans-dichloridobis(1-methyl-4-nitropyrazole)platinum(II) 2 has been presented, and the structure of the compound 2 has been confirmed by X-ray diffraction method. Cytotoxicity of the investigated compounds was examined in vitro on three human cancer cell lines (MCF-7 breast, ES-2 ovarian and A-549 lung adenocarcinomas) and their logP was measured using a shake-flask method. The trans complex 2 showed better antiproliferative activity than cisplatin for all the tested cancer cell lines. Additionally, trans-dichloridobis(1-methyl-5-nitropyrazole)platinum(II) 4 has featured a lower IC50 value than reference cisplatin against MCF-7 cell line. To gain additional information that may facilitate the explanation of the mode of action of tested compounds cellular platinum uptake, stability in L-glutathione solution, influence on cell cycle progression of HL-60 cells and ability to apoptosis induction were determined for compounds 1 and 2.